Bismuth subsalicylate in the treatment of H2 blocker resistant duodenal ulcers: role of Helicobacter pylori. Issue 2 (February 1992) - Wagner, S; Gebel, M; Haruma, K; Bär, W; Lange, P; Freise, J; Gladziwa, U; Schmidt, F W
Abstract : Fifty nine patients with Helicobacter pylori positive duodenal ulcers that failed to heal after a six week course of treatment with H2 blockers were randomly assigned to one of the following three regimens: (i) bismuth subsalicylate, 600 mg three times daily (n = 19), (ii) ranitidine, 300 mg at night (n = 20), (iii) bismuth subsalicylate plus ranitidine (n = 20). Cumulative ulcer healing rates after four and eight weeks respectively were as follows: bismuth subsalicylate 74% (14/19) and 95% (18/19), ranitidine 40% (8/20) and 65% (13/20), bismuth subsalicylate plus ranitidine 80% (16/20) and 95% (19/20). Bismuth subsalicylate treatment was better than ranitidine at both four and at eight weeks (p less than 0.05). The clearance rates for H pylori after four weeks were: bismuth subsubsalicylate 58%, ranitidine 0%, bismuth subsalicylate plus ranitidine 55%. After stopping bismuth therapy bacterial recrudescence frequently occurred. After bismuth treatment 86% (19/22) of ulcers had healed if H pylori had been cleared, whereas only 65% (11/17) had healed if H pylori persisted (NS). This study shows that bismuth subsalicylate is more effective in the treatment of resistant duodenal ulcers than standard dose ranitidine. It may be that suppression of H pylori by bismuth subsalicylate promotes ulcer healing.